DISASTER AND RESILIENCE FOR THE 2007 FLOOD EVENT IN PART OF SUKOHARJO REGENCY - Sinta Damayanti; Muh Aris Marfai (Faculty of Geography, Universitas Gadjah Mada, 2011)
Community resilience has become an important factor in a disaster mitigation plan.Resilience is related to the ability to recover from a disaster and is for every persondifferent. This research intends to assess community resilience for flood disaster. Factorsfor quantifying community resilience were asked to respondents by giving questionnaireand interviewing them, and FGD was also done in order to generate flood map based onthe community knowledge. The FGD result shows that the flood depth in the study areavaries from 0 until 300 cm, and the duration of inundation varies from 1-7 days. Floodalso caused losses, and the distribution of the losses was Rp. 0 - 100,000,000,- although, ingeneral, the losses was merely below Rp. 2,000,000,-. Based on the weighting result, theresilience value of the respondent is distributed from 0.113 until 0.700. The averageresilience value of Laban village is 0.403, and 0.368 for Kadokan village. The resiliencevalue was mostly influenced by human capital. In order to increase the communityresilience, government has established flood control devices and rehabilitated the dike alongthe river.